علامہ وحید الد یں خان کی"پیغمبرانقلاب "ا ور ڈاکٹر اسرا ر احمد کی "سیرت النبی صلى الله عليه وسلم " کے ا سالییب و مناہج کا تقابلی مطالعہ: A comparative study of the styles and approaches of Allama Wahid Uddin Khan's "Prophet of Revolution" and Dr. Israr Ahmed's "Sir-t-ul-Nabi" - BiBi , Nosheena; Parveen , Nazia (International Research Journal of Arabic and Islamic Studies, 2024)
In the academic history of Muslims, the knowledge of hadith and biography are two such aspects that no other nation and no other religion in the world can compete with. In the first of these two sciences, every aspect of Prophet Muhammad's pure speech, good deeds and way of life has been preserved with such firmness and care that even non-Muslims paid tribute to this scholarly and research effort of Muhaddeen. has presented As far as biography is concerned, every possible and necessary aspect of the Prophet's life has been preserved in such a way that a living and dynamic personality is preserved. From his childhood to his death, no corner was left out. In this context, the history of Hijaz and Arabia, Arab tribes and their genealogies, Arab history and geography, Arab civilization and cultural traditions, political and cultural map, literary and poetic capital and their characteristics and vices, all are provided in detail. has been done Many biographers have rendered services in the field of biography, among these biographers are Maulana Wahid Uddin Khan and Dr. Israr Ahmed who have rendered many services in the field of biography. So, in this article, the biographical services of Maulana Wahid Uddin Khan and Dr. Israr Ahmad have been described. Maulana Wahid Uddin Khan used to describe every incident of Sirat from all aspects. In the same way, Dr. Asrar Ahmad tries to describe all the events of Sirat exclusively in the light of Quran. Keywords: Prophet Muhammad ,صلى الله عليه وسلمAllama Wahid Uddin Khan’s, Dr Israr Ahmed, Study, Siret, Approaches.